GE_GERICHTE P/15912/2012 vom 25. März 2014 - GE Cour de justice (2014)
IN DUBIO PRO REO; DISPOSITIONS PÉNALES DE LA LSTUP; FIXATION DE LA PEINE; INDEMNITÉ(EN GÉNÉRAL); ACQUITTEMENT | CPP.10.3; LStup.19.1; LStup.19.2; CP.47; CPP.429.1